A study of occupational preferences of high school seniors in the Division of Antique - Villamon, Jesus N. 1912- ([Quezon City s.n.], 1963)
This is an investigation of the influences of factors inherent in the individual, family and school community, which affect occupational preferences of high school seniors in the division of Antique
Thesis (M.Ed.)--University of the Philippines
Keywords: Profession, Choice of